Prenylated flavones from Artocarpus altilis - Shamaun, Shireen Shaharina; Rahmani, Mawardi; Mohd Hashim, Najihah; Mohd Ismail, Hazar Bebe; Md. Sukari, Mohd. Aspollah; Ee, Gwendoline Cheng Lian; Go, Rusea (Springer, 2010)
Six prenylated flavones, including one new compound, were isolated and identified from the stem bark extracts of Artocarpus altilis. The new prenylated flavone hydroxyartocarpin (1) was characterized as 3-(c,c-dimethylallyl)-6-isopentenyl-5,8,20,40-tetrahydroxy-7-methoxyflavone and the known compounds were artocarpin (2), morusin (3), cycloartobiloxanthone (4), cycloartocarpin A (5) and artoindonesianin V (6). The structures of the compounds were determined by spectroscopic methods (IR, MS, 1H-NMR and 13C-NMR) and comparison with published data for the known compounds.